Experimental study on interfacial friction characteristics of composite geomembranes. Issue 5 (3rd September 2022) - Yang, Wu; Shi, Kebin; He, Jianxin
ABSTRACT: The interfacial friction characteristics of composite geomembranes have a significant impact on the stability of engineering structures. To comprehensively analyze the interfacial friction properties of composite geomembranes and cushion materials, the effects of shear material, roughness, shear rate, and test temperature were studied through laboratory direct shear friction tests. The results show the improved interface friction performance of the composite geomembranes and granular material. With the increase in the particle size of the test material, the friction angle of the plastic film surface decreased, and the friction angle of the cloth interface increased. The rougher the mortar surface, the greater the interfacial friction angle. The faster the shear rate, the larger the interfacial friction angle. The higher the test temperature, the smaller the interfacial friction angle. The research results provide a theoretical basis for the design of anti-seepage forms of dam bodies, and serve as a reference for engineering designers in evaluating the stability of dam slopes. Graphical Abstract: uf0001